Gastric schwannoma, a benign neoplasm hiding as gastrointestinal stromal tumour - Osama Ahmed Qureshi; Sheeraz Ur Rehman; Shahrukh Khalil; Yousra Zahid (Journal of the Pakistan Medical Association, 2022)
Gastric Schwannomas are rare, submucosal mesenchymal tumours arising from the nerve plexus of the Gut wall. They have an incidence rate of 0.2% of all Gastric tumours. They are mostly asymptomatic, but can present with vague gastrointestinal symptoms and the fact that histopathologically, they are similar to Gastrointestinal stromal tumours, so they are most often misinterpreted as Gastrointestinal stromal tumours. We present a case, which was also hiding as GIST (Gastrointestinal stromal tumours) preoperatively, on the basis of Endoscopic and Radiological investigations. The diagnosis was then confirmed as Gastric Schwannoma, postoperatively by immunohistochemical analysis. Hence, it is important to diagnose correctly to make appropriate treatment decisions. The findings presented here can may be helpful for a clinician for diagnosing a Gastric Schwannoma. Keywords: Gastrointestinal Stromal Tumours, Endoscopes, Stomach Neoplasms, Immunohistochemistry, Care, Postoperative.